The leadership of the Kiai in Facing the Globalization of Education in Islamic Boarding School - Taufiq, Ahmad (Universitas Negeri Malang, 2021)
Abstract: The leadership of the Kiai is very important in the management of Islamic boarding schools, especially the salafiyah Islamic boarding schools, which of course depend heavily on the leadership of the Kiai. The flow of globalization which is a very fast change also affects the pattern of education and of course Islamic boarding schools as one of the national education entities. The influence of globalization in Islamic boarding schools mainly occurs in the pattern of education and leadership models which also affect all aspects of pesantren life. This change also occurred in the Salafiyah Islamic boarding school, which eventually implemented paperless learning because some books had become e-books that could be edited for student learning. In the end, Kiai's leadership became a milestone in the rise of Islamic boarding schools in the era of globalization.